(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The research on the phenomenon of variantivity in natural languages should comprise all their subsystems. Much attention has been given to phonetic, morphological, lexical, phraseological phenomena, while strictly paremiological ones have been handled to a lesser extent to date. The discussed issue of proverbial innovations in the contemporary Polish language partly fills in the research gap. The factographic material collected in the paper has shown a significant nominative and expressive potential of paremic units fulfilled as a result of numerous modifications of the canonical form of the proverbs used commonly in the Polish language. The said results could be obtained from the paremiological material excerpted with the use of www.google.com search engine in generally available online resources. The criterion adopted for selecting the initial units was the indicator of their frequency based on the socalled paremiological minimum. Afterwards, a secondary modified proverb was compared to its original, which enabled a description of basic innovation mechanisms and identification of the function of a specific registered innovation.